Green Finance Supports Sustainable Environment: Empirical Approach towards Applicability in Tourism Sector - MOHANTY, Rojalin; SAMAL, Ansuman; KUMAR, Rakesh (Theoretical and Practical Research in Economic Fields; Vol 15 No 1 (2024): TPREF, Volume XV, Issue 1(29), Spring 2024, 2024)
Purpose . Sustainable development Goal (SDG)-2030 is an important agenda of UN. Green finance concept is a way to support sustainable development goal. This research explore concept of green finance toward green industry in India. The aim of this study how green finance help in increase of green industry in Indian region focusing on the tourism sector specifically. Methodology. The study based on empirical research structure equation model constructed with help of SPSS and AMOS software. Data collected from respondent those are related to manufacturing company and availed green finance services from financial institute. Total 576 sample collected within Indian region. Finding. The study finds that green finance awareness, incentive, initiative and technology will increase green industry. The study finds that factors of green finance industries are green marketing initiative, green finance incentive, awareness about green finance and technology innovations. Originality . The study based of five factor these are green finance marketing initiative, green finance incentive to investor, green finance awareness, green technology innovation and green investment. All these factors support green industry in Indian region and other region as well. Practical implications . The aim of the study to fids out factors which increased green industry through green finance supports. The study related to finance services for green investment for sustainable society.